CLIMATE CHANGE LITIGATION IN INDONESIA: CORPORATE LIABILITY AND STATE RESPONSIBILITY AS CLIMATE CHANGE MITIGATION TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS - Ni Wayan Wirawati; Soeparto Wijoyo; Agus Yudha Hernoko (Faculty of Law, Universitas Pekalongan, 2025)
Global climate change due to environmental damage departed from an understanding on the anthropocentrism perspective onenvironment making human beings the center of everything on earth and thereby exploiting the natural resource as much as possible. The unwise exploitation of land in Indonesia results in forest or land fire exerting the effect of globalwarming leading to global climate change and endangering the life, particularly the fulfillment of human rights to good andhealthy living environment. Corporate liability and state responsibility are two important points in addressing the climate change in Indonesia. Indonesia has been committed to contributing to addressing climate change by ratifying an international agreement, Paris Agreement, to reduce greenhouse gas emission and to actively prevent climate change. The enforcement of environmental law through litigation is carried out using various mechanisms for filing environmental lawsuit to demand compensation for economic and ecological losses and restoration of environmental damage against corporation